Significance of Marangoni convection in ethylene glycol base hybrid nanofluid flow with viscous dissipation through a porous medium - Ali Rehman; Ilyas Khan; Sultan Alshehery; Muhammad Sabaoon Khan (Scientific Reports)
Abstract The current research deals with analytical analysis of Marangoni convection on ethylene glycol base hybrid nanofluid two-dimension flow with viscous dissipation through a porous medium, which have some important application in mechanical, civil, electronics, and chemical engineering. Two types of nanoparticles one is sliver and other is graphene oxide and ethylene glycol is used as base fluid in this research work. The authors applied appropriate transformations to convert a collection of dimension form of nonlinear partial differential equations to dimensionless form of nonlinear ordinary differential equations. The transformed nonlinear ordinary differential equations are solved with the help of an approximate analytical method known as the homotopy analysis method. The effects of various parameters, including nanoparticle volume fraction, porosity parameter, Marangoni convection, and Eckert number, on energy and momentum profiles are analyzed, with the results illustrated using graphs. A physical explanation is provided to simulate and evaluate the behavior of nanofluid structures, such as temperature and velocity, in response to changes in these influencing factors.